A theoretical overview of land reform - KABACHE, Rabah (Journal of Human Sciences, 1999)
The main aim of this paper is to examine the objectives of land reform in the underdeveloped countries, and it argues that land reform tends to have socio-economic  and political implications for the power relationships between various social groups in society. And, in an attempts to elaborate this argument, I see that the success of any land reform depends on the intended beneficiaries and on their positions to influence political decisions. This paper ends with the major objective of land reform is to make peasants masters of their own concerns and responsible for their destiny.